Improving the thermoelectric performance of ZrNi(In, Sb)-based double half-Heusler compounds. Issue 25 (15th June 2022) - He, Shiyang; Bahrami, Amin; Ying, Pingjun; Giebeler, Lars; Zhang, Xiang; Nielsch, Kornelius; He, Ran
Abstract : Discovery of ZrNi(In, Sb)-based double half-Heusler compounds with low lattice thermal conductivity and high thermoelectric performance. Abstract : The complexity of crystal structures plays an intriguing role in manipulating properties in thermoelectrics, spintronics, and batteries. In comparison to the widely studied ternary half-Heusler thermoelectric compounds, quaternary double half-Heusler compounds are promising due to their intrinsically low lattice thermal conductivities ( κ L ). However, they have been much less investigated due to the limited material availability. In this study, we report a new double half-Heusler compound based on ZrNi(In, Sb). Upon tuning the ratio of In/Sb from 0.5/0.5 to 0.4/0.6 and reducing the nominal concentrations of Zr and Ni by 10%, we greatly reduce the intensities of the impurity-phase peaks in the diffraction patterns. An even better phase purity, in combination with an optimized power factor, is realized by substituting Co at the Ni sites. Further alloying Hf at the Zr sites enhances the point defect scattering of phonons, which yielded a minimum κ L of ∼1.8 W m −1 K −1 and a maximum zT of ∼0.5 for Zr0.7 Hf0.2 Ni0.65 Co0.25 In0.4 Sb0.6 at 973 K. Our work thus confirms the intrinsically low κ L of ZrNi(In, Sb) double half-Heusler compounds and indicates their promising applications upon further improving their electrical transport properties.